Kecemasan berbicara di depan umum pada mahasiswa pasca pandemi: Bagaimana peran body image? (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to determine the relationship between body image and public speaking anxiety among students at the University of 17 August 1945 Surabaya. The method in this research is quantitative research using purposive sampling technique. The subjects of this study were 408 UNTAG Surabaya students from class 2018 to class 2022 which were calculated using the slovin formula with a 5% error margin and using a Likert scale instrument. The research data was taken with a body image scale of 28 items and a scale of anxiety to speak in public depths of 25 items. Data analysis in this study used Product Moment correlation with the help of IBM SPSS Statistics 20 and obtained a result of -0.347 with a significance of p=0.000. That is, there is a negative relationship between body image variables and public speaking anxiety among students at the University of 17 August 1945 Surabaya. The more positive the body image the students have, the lower the tendency for anxiety to arise in public speaking among students at the University of 17 August 1945 Surabaya. On the other hand, the more negative the body image a student has, the higher the tendency for public speaking anxiety to arise among students at the University of 17 August 1945 Surabaya.